Trans-Oral Robotic Surgery: 14 Cases of Pleomorphic Adenoma of the Parapharyngeal Space. Issue 5 (27th July 2022) - Salzano, Giovanni; Togo, Giulia; Maglitto, Fabio; Borriello, Gerardo; Perri, Francesco; Audino, Giovanni; Vaira, Luigi Angelo; Maglione, Maria Grazia; Petrocelli, Marzia; Califano, Luigi; Ionna, Franco
Abstract : Purpose: The aim of this study has been to describe our experience with pleomorphic adenomas of the parapharyngeal space (PPS) treated with trans-oral robotic surgery (TORS). Tumors arising from the PPS comprise less than 0.5% of all head and neck tumors. Salivary gland tumors account for 40% to 50% of PPS lesions with pleomorphic adenomas representing the most common salivary tumors (80%–90%). Parapharyngeal space tumors cause nonspecific symptoms and may be difficult to diagnose. Methods: In our study a preoperative diagnosis was conducted by fine needle aspiration biopsy and magnetic resonance imaging and the results were used to plan the correct surgical approach. Results: In all cases we were able to employ TORS, a minimally invasive procedure that allows us to operate in narrow and anatomically complex spaces that we can only reach thanks to the use of well-articulated hand pieces. Conclusions: This report indicates that TORS is a safe surgical procedure for the excision of benign tumors of the PPS in selected cases.